The impact of e-procurement system qualities and trust on end-user satisfaction / Manal M. N. Sharabati - Sharabati, M. N.Manal (2014)

(untitled)
The main aim of this study is to investigate the impact of the e-procurement system qualities and trust on the e-procurement system end-user satisfaction, in a mandatory system environment. In line with this objective, three research questions are established: First, what are the e-procurement system qualities that influence trust and end-user satisfaction? Second, what is the impact of trust on end-user satisfaction? Third, does trust mediate the relationship between e-procurement system qualities and end-user satisfaction? This study postulates that suitable e-procurement system qualities and trust, as perceived by system end-users, have influence on the e-procurement system end-user satisfaction. IS success model is adopted to describe the causal linkages between the determinants that affect e-procurement system end-user satisfaction. This research study investigates end-user’s experiences with e-procurement system and their impact on user’s belief ‘trust’ to evaluate e-procurement system end-user satisfaction. The users’ experiences are classified into direct user’s experience with the system, represented by perceived e-procurement system quality construct, and indirect user’s experiences, represented by perceived order fulfillment quality of suppliers as perceived by system end-users [‘buyers’]. A questionnaire that reflects the proposed framework constructs is developed to collect the primary data for the study. The data is collected from 432 e-procurement system users who are working at the purchasing departments in Malaysian governmental Ministries, Agencies, and Departments. This study is quantitative with a deductive approach. It employs partial least squares structural equation modeling (PLS- iii SEM) to validate and confirm research model to test the relationships being hypothesized. The findings of this study provide empirical evidence for the significant impact of perceived e-procurement system quality, perceived order fulfillment quality, and trust on e-procurement end-user satisfaction. Furthermore, the study findings approve the influence of both system qualities, namely perceived e-procurement quality and perceived order fulfillment quality on trust. The findings reveal that perceived e-procurement quality positively influences perceived order fulfillment quality. Finally, trust is found to have partial mediating effect between system qualities and e-procurement system end-user satisfaction.